Bilevel Peer-to-Peer Energy Trading to Maintain Network Quality and Benefit Distribution - Noorfatima, Nadya; Jung, Jaesung; Onen, Ahmet; Yoldas, Yeliz (IEEE Transactions on Applied Superconductivity, 2024)
The expansion of peer-to-peer (P2P) energy trading induces more complicated operations not only in physical terms as in network quality but also in economic terms as in benefit distribution. Therefore, this study proposes a framework that considers the network quality problem in the market operation and maintains the optimal benefit distribution for the expanding P2P system. For this, the network quality is measured by maintaining the voltage level of each corresponding node within the voltage limits. To integrate two objectives, a cluster-based bilevel P2P energy trading is incorporated with distributed optimization. Therefore, the alternating direction method of the multipliers is applied to integrate the objectives and provide communication between the two levels of P2P with limited information exchanges. The results demonstrate that the proposed method can improve the voltage level as a representation of network quality and attract many participants as an impact of proper benefit distribution even in the expanding P2P system.
Keywords: Benefits distribution; Bilevel; Bilevel peer-to-peer energy trading; Distributed optimization; Energy trading; Kirschen network cost allocation; Network cost allocation; Network qualities; Network reliability; Peer to peer; Bilevel peer-to-peer energy trading; distributed optimization; game theory; Kirschen network cost allocation; network reliability